2020
DOI: 10.3390/nano10091768
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Flexible All-Solid Supercapacitors with Direct Sputter-Grown Needle-Like Mn/MnOx@Graphite-Foil Electrodes and PPC-Embedded Ionic Electrolytes

Abstract: Recent critical issues regarding next-generation energy storage systems concern the cost-effective production of lightweight, safe and flexible supercapacitors yielding high performances, such as high energy and power densities as well as a long cycle life. Thus, current research efforts are concentrated on the development of high-performance advance electrode materials with high capacitance and excellent stability and solid electrolytes that confer flexibility and safety features. In this work, emphasis is pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…To make the electrolyte viscous, this electrolyte was stirred for another 2 h at room temperature and finally used it for MSC device fabrication. The preparation of this PGE has been followed from one of our previous works [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…To make the electrolyte viscous, this electrolyte was stirred for another 2 h at room temperature and finally used it for MSC device fabrication. The preparation of this PGE has been followed from one of our previous works [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Supercapacitors (SCs) can store energy via redox reaction or the formation of electric double layers (EDLs) of ionic species over the surface of electrodes at the electrode/electrolytes interface. They can reach the global requirements for ESS due to rapid power output, fast charge–discharge ability and longer lifetime than batteries [ 4 , 120 , 121 , 122 , 123 ]. SCs can be independently used as an alternative renewable energy source in the place of batteries in many fields such as wearable electronics, electric buses, laptops, mobiles, aerospace and various diagnostic instruments in medical systems, which boosts the growing interests in the field of advanced SCs research.…”
Section: Ionic Liquids (Ils) For Supercapacitors (Scs)mentioning
confidence: 99%
“…In another work, Ray, A. et al reported a PPC polymer embedded (EMIM)(TFSI) ILs-based electrolyte for direct sputter-grown Mn/MnO x @Graphite-Foil electrodes of flexible all-solid supercapacitors. This PPC embedded ILs exhibited a wide electrochemical stable potential window of up to 2.2 V with a long cycle life stability of up to 5000 cycles for this flexible needle-like Mn/MnO x nanostructured on the surface of graphite foil [ 120 ]. In the case of the increased energy density of SCs, the shape and morphology of the electrodes play an important role for the electrolyte.…”
Section: Ionic Liquids (Ils) For Supercapacitors (Scs)mentioning
confidence: 99%
“…As a result, by decreasing the effects of supercapacitors’ self-discharge voltage, the lifespans of devices that depend on the power supply of supercapacitors are improved [ 28 , 29 ]. Like batteries, different materials for the construction of supercapacitors have been used, and the development of models has been implemented as a strategy to decrease the self-discharge voltage [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%